1986
DOI: 10.1002/j.1551-8833.1986.tb05731.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Temperature on the Removal of Trihalomethane Precursors by Coagulation

Abstract: This study showed that the trihalomethane (THM) concentration in finished water that had ken treated at 35.6" F (2°C) was significantly lower than in water treated at 71.6" F (22°C). Water temperature did not appear to affect the removal of total organic carbon (TOC) during coagulation with metal ion salts, but color removal was slightly reduced at low temperatures. The efficiency of coagulation for removing TOC, color, and THM formation potential improved when the water was treated at pH 5 rather than pH 7, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 8 publications
0
15
1
Order By: Relevance
“…In our study the temperature value of the drinking water ranged from 7.20°C to 22.70°C, which was associated with the formation of THM values in a wide range of 48.0/.tg/L to 102.0/.tg/L. A study by Knocke et al [30] indicated that the rate of THM formation at 2°C was normally 60-70% less than observed at 22°C.…”
Section: Effect Of Temperaturecontrasting
confidence: 54%
“…In our study the temperature value of the drinking water ranged from 7.20°C to 22.70°C, which was associated with the formation of THM values in a wide range of 48.0/.tg/L to 102.0/.tg/L. A study by Knocke et al [30] indicated that the rate of THM formation at 2°C was normally 60-70% less than observed at 22°C.…”
Section: Effect Of Temperaturecontrasting
confidence: 54%
“…Temperature also significantly affects turbidity and particle counts during coagulation (Braul et al, 2001). However, dissolved organic carbon (DOC) and colour removal are not sensitive to temperature (Knocke et al, 1986;Hanson and Cleasby, 1990;Randtke, 1998).The The negative effect of temperature tends to be greatest with dilute suspensions. Direct filtration and DAF processes are much less affected by cold-water temperatures than sedimentation .…”
Section: Natural Cationic Polymermentioning
confidence: 99%
“…This differed from the hydrolysis behavior of Al when applied alone (Safarikova et al, 2013). This is attributed to the higher affinity of released proteins to Al species than to iron compounds (Pivokonsky et al, 2006), which might also explain the greater efficiency of iron salts in terms of DOC removal (Knocke et al, 1986). Similarly, introducing Fe(II) into the pre-treatment improved the precipitation of Al salts (Fig.…”
Section: Hydrolysis Mechanisms Of Fe and Al As Dualcoagulantmentioning
confidence: 73%
“…The combined use of different coagulants might be especially desirable in algae coagulation. Aluminum exhibited higher efficiencies in terms of the removal of turbidity, bacteria, and color than iron salts did (Cheng et al, 2003), whereas iron salts were better than aluminum towards the removal dissolved organic carbon (DOC) (Cheng et al, 2003;Knocke et al, 1986). The treatment of algae-burdened water not only involves the removal of suspended algae cells but also that of soluble DOM, the dualcoagulant approach can be advantageous in this case.…”
Section: Introductionmentioning
confidence: 99%